DISTAL PERFUSION IS MAINTAINED IN VETERAN SUBJECTS UNDERGOING TRANSRADIAL CARDIAC CATHETERIZATION - Durham, Katherine Anne; Piano, Marianne; Griza, Decebal S.; Ahmed, Kashif; Shafi, Amtul; Vidovich, Mladen (Journal of the American College of Cardiology, 2017)
Methods: Using repeated measures design, artery diameters and hand temperatures were measured before (pre) and 30 days post RTA in a convenience sample of Veteran subjects (N=76). Since thermography is an indirect technique for measuring blood flow, radial artery diameter was confirmed by ultrasound (US) pre and post TRA.